2020
DOI: 10.3390/bios10030025
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable SERS-Based Immunoassay Guided by Photocatalytic Performance of Fe3O4@TiO2@Au Nanocomposites

Abstract: A novel recyclable surface-enhanced Raman scattering (SERS)-based immunoassay was demonstrated and exhibited extremely high sensitivity toward prostate specific antigen (PSA). The immunoassay, which possessed a sandwich structure, was constructed of multifunctional Fe3O4@TiO2@Au nanocomposites as immune probe and Ag-coated sandpaper as immune substrate. First, by adjusting the density of outside Au seeds on Fe3O4@TiO2 core-shell nanoparticles (NPs), the structure-dependent SERS and photocatalytic performance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The diagnostic methods could achieve the simultaneous detection of dual PSA biomarkers within the gray zone between 4.0 and 10.0 ng/mL for clinical samples. Jiang et al constructed an Fe3O4@TiO 2 @Au nanocomposite immunoprobe with a detection limit of 1.871 pg/mL LOD for PSA [ 64 ]. Notably, the SERS immunoprobe can be recycled multiple times due to the excellent catalytic properties of TiO 2 .…”
Section: Bio-functionalization Engineering For Sers Biosensingmentioning
confidence: 99%
“…The diagnostic methods could achieve the simultaneous detection of dual PSA biomarkers within the gray zone between 4.0 and 10.0 ng/mL for clinical samples. Jiang et al constructed an Fe3O4@TiO 2 @Au nanocomposite immunoprobe with a detection limit of 1.871 pg/mL LOD for PSA [ 64 ]. Notably, the SERS immunoprobe can be recycled multiple times due to the excellent catalytic properties of TiO 2 .…”
Section: Bio-functionalization Engineering For Sers Biosensingmentioning
confidence: 99%
“…Microparticles with a core of Fe 3 O 4 coated with a layer of TiO 2 and then with Au nanoparticles (Fe 3 O 4 @TiO 2 @Ag microparticles) were investigated as a recyclable substrate for a SERS-based PSA immunoassay [ 68 , 69 ]. It was found that the photocatalytic degradation of the microparticles could be adjusted by tuning the thickness of the middle TiO 2 shell and the density of the Ag nanoparticles at the outer surface, while the magnetic properties of the Fe 3 O 4 core enhanced the photocatalytic activity of the microspheres [ 68 ].…”
Section: Cancer Biomarkers Immunochemical Detection Via Sersmentioning
confidence: 99%
“…A LOD of 16.25 pg/mL was claimed, and a linear dynamic range from 0.1 ng/mL to 100 μg/mL [ 68 ]. Microspheres with the same structure have also been employed as labels in a non-competitive PSA immunoassay after their modification with the Raman tag 4-MBA and an anti-PSA antibody [ 69 ]. SiC sandpapers with sputtered Ag films were used as substrates after modification with an anti-PSA antibody.…”
Section: Cancer Biomarkers Immunochemical Detection Via Sersmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many researchers have begun to focus on the chemical enhancement mechanism of SERS. The charge transfer (CT) enhancement related with semiconductor materials is used in these studies. Because intermolecular interactions can alter the electron density distribution and the Raman scattering cross section, SERS would improve the different Raman vibration modes of probe molecules and detection specificity. In previous studies, the CT and EM mechanisms were often discussed separately. There has been a lack of effective methodology for combining the two mechanisms into a single-material system to design the most efficient SERS substrate.…”
Section: Introductionmentioning
confidence: 99%